COMPETENCE, DISCIPLINE, AND WORK ENVIRONMENT ON THE EMPLOYEE PERFORMANCE OF DEPARTMENT OF PUBLIC WORKS AND SPATIAL PLANNING SURAKARTA - Aan Tejo Yulianto; Istiatin Istiatin; Bambang Mursito (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The purpose of this study was to analyse the effect of competence, discipline, and work environment on the employee performance of Department of Public Works and Spatial Planning Surakarta. The survey approach used is descriptive quantitative, and the survey data used are primary and secondary data. The sample strategy utilized in this study is a saturated sampling strategy with 70 respondents. Multiple linear regression, F test, t test and coefficient of determination (R2) are used to analyze the data. The survey results shows that competence, discipline, and work environment has a significant effect on the employee performance of Department of Public Works and Spatial Planning Surakarta. The results of the coefficient of determination test obtained the Adjusted R2 value of 0,566 or 56,6%, indicating that employee performance in the Department of Public Works and Spatial Planning Surakarta is influenced by competence, discipline, and work environment variables, while the remaining 43,4% is explained by other variables.